2023
DOI: 10.3389/fendo.2023.1179521
|View full text |Cite
|
Sign up to set email alerts
|

Global biomarkers of oxidative stress and fractures: a matched case-control study

Abstract: BackgroundEvidence for a relationship between oxidative stress and osteoporotic fractures in humans is limited. Fluorescent oxidation products (FlOPs, excitation/emission wavelengths 320/420nm denoted FlOP_320; 360/420nm [FlOP_360]; and 400/475nm [FlOP_400]) are global biomarkers of oxidative stress, and reflect oxidative damage to proteins, phospholipids, and nucleic acids. We investigated the association between FlOPs and a recent osteoporotic fracture.MethodsWe conducted a case-control study in a Chinese po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…Consistent with a previous study ( 16 ), we included the following covariates in this study: demographics (sex and age), lifestyle factors (e.g., physical activity, smoking status, milk intake >1 time/week and calcium supplement), postmenopausal status in females, disease history (e.g., coronary heart disease, type 2 diabetes, stroke), height loss of more than 3 cm after age 40 years, falls from standing height or less within the last 12 months, family history of osteoporosis and fractures, and body mass index (BMI). These factors were included because they were major risk factors for fractures ( 17 , 18 ).…”
Section: Methodssupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with a previous study ( 16 ), we included the following covariates in this study: demographics (sex and age), lifestyle factors (e.g., physical activity, smoking status, milk intake >1 time/week and calcium supplement), postmenopausal status in females, disease history (e.g., coronary heart disease, type 2 diabetes, stroke), height loss of more than 3 cm after age 40 years, falls from standing height or less within the last 12 months, family history of osteoporosis and fractures, and body mass index (BMI). These factors were included because they were major risk factors for fractures ( 17 , 18 ).…”
Section: Methodssupporting
confidence: 93%
“…Similar to our previous study ( 16 ), incident cases were confirmed to be new fractures in the Second Hospital of Jilin University in 2020. Using the survivor sampling methods, we selected controls from a community-based generally healthy population who had no history of fracture in Changchun, Jilin in 2020.…”
Section: Methodssupporting
confidence: 88%
See 2 more Smart Citations